Genetic Potential of Agronomic Traits and Seed Physicochemical Properties of Novel Jatropha Lines Developed from Complex Interspecific Hybridization - Narathid Muakrong; Peerasak Srinives (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2020)
Fifteen jatropha lines were obtained from complex crossing between progenies derived from interspecific hybridization of Jatropha curcas and J. integerrima. They were evaluated for variability and association in yield, yield components, oil content, fatty acid composition, phorbol esters content, and growth characters. The major fatty acids in seed were oleic and linoleic acids, with a negative correlation among them. Seed yield showed a positive correlation with number of fruits per inflorescence and seeds per fruit, 100 seed weight and canopy size. A path coefficient analysis showed that number of fruits per inflorescence and canopy width had high positive direct relationship with seed yield per plant. Most characters showed high broad-sense heritability. Clustering by traits classified the breeding lines into five groups with a large distance between groups. The members in each group comprised lines of the same or similar pedigrees. Cluster I was the high seed yield group comprising two accessions (KUJL23 and KUJL18). Clustering based on principle components classified them into four groups. The lines in cluster II and III from cluster analysis were included in one group, while members of the other groups were the same in both clustering methods.